Conductive filament formation at grain boundary locations in polycrystalline HfO2 -based MIM stacks: Computational and physical insight. (September 2016) - Shubhakar, K.; Mei, S.; Bosman, M.; Raghavan, N.; Ranjan, A.; O'Shea, S.J.; Pey, K.L.
Abstract: Resistive switching in high-κ (HK) dielectric based metal-insulator-metal (MIM) devices occurs locally and is accompanied by dynamic changes in the structural and electrical properties of the HK dielectric. In polycrystalline HfO2 HK dielectric based MIM devices, grain boundaries (GBs) play a significant role in the formation of a percolation path for the resistive switching as the GB regions contain a large number of defects and favor the formation of conductive/low resistive paths. In this work, we present a multi-physics based combined Kinetic Monte Carlo-Finite element model (KMC-FEM) 3D percolation framework to simulate the resistive switching (high resistive state (HRS) to low resistive state (LRS)) process in TiN/HfO2 (5 nm)/Pt MIM stacks. The KMC-FEM model describes the effect of GBs on the formation of conductive path during the HRS to LRS resistive switching. In addition, this model is used to find the statistical distribution of conductive filament/path formation in amorphous and polycrystalline HfO2 dielectrics. Conductive atomic force microscopy and transmission electron microscopy observations on the characteristics of the HfO2 dielectrics at the nanometer scale complement the simulation results. The results clearly show that the HRS to LRS resistive switching occurs preferably at the GB regions in polycrystalline HfO2 and at random locations in amorphous HfO2 -based MIM stacks.